Impact of filmless imaging on the frequency of clinician review of radiology images - Reiner, Bruce I. (Springer-Verlag, 1998)
The purpose of this study was to determine the impact of filmless imaging on the frequency with which physicians access radiology images and to assess clinician perception of image accessibility using a hospital-wide Picture Archival and Communication System (PACS). Quantitative data were collected at the Baltimore VA Medical Center (BVAMC), prior to and after conversion to filmless imaging, to determine the frequency with which clinicians access radiology images. Survey data were also collected to assess physician preferences of image accessibility, time management, and overall patient care when comparing filmless and film-based modes of operation. In general, there was a significant increase in the average number of radiology images reviewed by clinicians throughout the hospital. However, the one area in the hospital where this trend was not observed was in the intensive care unit (ICU), where the frequency of image access was similar between film and filmless operations. Ninety-eight percent of clinicians surveyed reported improved accessibility of images in a filmless environment resulting in improved time management. The mean clinician estimate of time saved due to the use of PACS was 44 minutes. The study documented a combination of clinician perception of improved accessibility and substantial time savings with the use of a hospital-wide PACS, which was supported by objective measurements. The increased frequency of image review by clinicians and rapid image access should provide a further impetus to radiologists to decrease report turnaround time to provide “added value” for patient care.